Characteristics and quality of cashew (Anacardium occidentale) seeds across various agroecological conditions - MUHAMMAD H. ANUGRAH; MELATI MELATI; AGUS PURWITO; ENDAH RETNO PALUPI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Anugrah MH, Melati, Purwito A, Palupi ER. 2024. Characteristics and quality of cashew (Anacardium occidentale) seeds across various agroecological conditions. Biodiversitas 25: 4406-4415. Cashew (Anacardium occidentale L.; Anacardiaceae) is a major plantation commodity developed mainly on marginal lands in Eastern Indonesia. This commodity is cultivated in various agroecological conditions, including wet, moderate, and dry climates. This research aims to provide information on the characteristics and quality of cashew seeds from different agroecological conditions and to explore the relationship between these conditions and seed storability. The research was conducted from November 2022 to December 2023. Seeds from two varieties were collected from seed orchards in various agroecological conditions. Seeds of Balakrisnan 02 variety were collected from a wet climate region (Bantul, Yogyakarta), and a moderate climate region (Sumbawa, West Nusa Tenggara). Seeds of Flotim variety were collected from a moderate climate region (Bangkalan, East Java), and a dry climate region (East Flores, East Nusa Tenggara). The seeds were stored at 16°C and 50% RH for six months. Physical, and physiological quality were observed during the storage. The result showed that drier agroecological conditions produce better physical quality seeds, such as larger seeds with thicker nut shells (fruit skin), and higher peroxidase activity and proline content. Planting the Balakrisnan 02 variety in moderate climate regions produces seeds with higher viability and vigor and longer storage capacity than those in wet climate regions. Meanwhile, Flotim, the drought-tolerant variety, when planted in the dry climate region produces seeds with higher viability but lower vigor and shorter storage capacity than those in moderate climate regions. Despite the differences in seed quality, planting the same variety in different agroecological conditions is still recommended to ensure seed availability due to different harvest times.